"I Play So I Am?" A Gender Study into Stereotype Perception and Genre Choice of Digital Game Players. Issue 2 (2nd April 2016) - Vermeulen, Lotte; Van Looy, Jan
Abstract : Stereotypes in game culture are still inhibiting the freedom of female players. This survey study aims to gain insight into these practices by looking at gaming stereotypes on two different, yet interrelated, levels. First, we inquire into perceptions of gamers regarding gender-related and general gamer stereotypes and how these relate to playing frequency. Second, genre choice is investigated in light of player's gender and how this is associated with play motivations. Results suggest that high frequency female players disagree the most with gender-related stereotypical beliefs and that these women are more strongly drawn towards specific gaming genres than men.